PREVALENCE AND IDENTIFICATION OF BACTERIA CAUSING ASYMPTOMATIC BACTERIURIA IN PREGNANT WOMEN AT ANTANG COMMUNITY HEALTH CENTER, MAKASSAR CITY - Hartati, Hartati; Misnarliah, Misnarliah (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Asymptomatic bacteriuria in pregnancy carries significant risks to maternal and fetal health. Untreated cases can progress to symptomatic urinary tract infections, prematurity, low birth weight, and fetal death. Data on the prevalence and types of bacteria causing asymptomatic bacteriuria in pregnant women, especially in Makassar, are still very limited. This study aims to determine the prevalence of asymptomatic bacteriuria and the types of bacteria causing it in pregnant women at the Antang Community Health Center in Makassar. This study is a quantitative descriptive study, using microbiological examination methods through urine dipstick testing, urine culture, and identification. The subjects were 58 pregnant women without symptoms of urinary tract infections who underwent pregnancy checkups at the Antang Community Health Center in Makassar. The sample used was a mid-stream urine specimen. Based on the demographic characteristics of pregnant women in their first, second, and third trimesters at the Antang Health Center in Makassar City, it shows that the majority of respondents are young pregnant women in the final stages of pregnancy (third trimester). Based on the results of the dipstick examination, it shows that the majority of respondents do not have an increase in leukocytes, which indicates a low possibility of urinary tract infections among pregnant women in their first, second, and third trimesters at the Antang Health Center in Makassar City. The results of urine culture showed that 2 samples with positive dipstick results for leukocyte esterase and nitrite parameters had bacterial colonies of >100,000 CFU/mL. The prevalence of asymptomatic bacteriuria in pregnant women in their first, second, and third trimesters at the Antang Health Center in Makassar City in this study was 3.45%. The types of bacteria that cause it are Escherishia coli and Klebsiella pneumoniae.